Institutional Approaches to Evaluate Teaching Effectiveness: The Role of Summative Peer Review of Teaching for Promotion and Tenure - Godbout-Kinney, Keif; Watson, Gavan P. L. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
A growing body of literature has identified student evaluations of teaching (SETs) as introducing bias against minority faculty members and not serving as a reliable or valid measure of teaching effectiveness. This lack of reliability and validity presents issues for university tenure and promotion committees, as these institutional processes necessarily require accurate, objective, and holistically informed modes of evaluation to recognize teaching achievements. Summative peer review of teaching (SPRT) is an alternative mode of assessment that aims to provide evidence of teaching effectiveness to inform promotion and tenure. SPRT, as an institutional practice, has been adopted at a small cohort of institutions of higher education, marking a potential shift in practice. This article examines SETs to articulate the problematic elements introduced by SETs, specifically to examine if SPRT can serve as a viable alternative. By describing the SPRT processes that four institutions have taken, the authors aim to articulate these emerging approaches to collecting evidence of teaching effectiveness. In this descriptive work, it is our secondary contention that SPRT, through intentional design and facilitation, can offer a process that does not introduce bias in the same way as SETs and thus, can also be used to satisfy the growing need for practices that help achieve, in part, institutional goals related to equity, diversity, and inclusion (EDI).